2013
DOI: 10.1063/1.4801505
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of bubble tip velocity in classical Rayleigh-Taylor instability at arbitrary Atwood numbers

Abstract: In this research, the temporal evolution of the bubble tip velocity in Rayleigh-Taylor instability (RTI) at arbitrary Atwood numbers and different initial perturbation velocities with a discontinuous profile in irrotational, incompressible, and inviscid fluids (i.e., classical RTI) is investigated. Potential models from Layzer [Astrophys. J. 122, 1 (1955)] and perturbation velocity potentials from Goncharov [Phys. Rev. Lett. 88, 134502 (2002)] are introduced. It is found that the temporal evolution of bubble t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In view of its direct consequence in various applications, the effects of initial perturbations are being explored extensively [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . Miles et al 21 investigated the effect of initial conditions on two-dimensional (2D) Rayleigh-Taylor instability (RTI) and transition to turbulence in planar blast-wavedriven systems, and found that the initial conditions have a strong effect on the time to transition to the quasi-self-similar regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of its direct consequence in various applications, the effects of initial perturbations are being explored extensively [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . Miles et al 21 investigated the effect of initial conditions on two-dimensional (2D) Rayleigh-Taylor instability (RTI) and transition to turbulence in planar blast-wavedriven systems, and found that the initial conditions have a strong effect on the time to transition to the quasi-self-similar regime.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the time when the instability reaches a mean quadratic growth depends on the initial perturbation shape, and the subsequent vortical interactions are also very sensitive to details of the initial perturbation shape. Liu et al 29 found that the temporal evolution of the bubble tip velocity is sensitively dependent on the Atwood numbers, the initial perturbation amplitude and the initial perturbation velocity in classical RTI. McFarland et al 30 investigated the effects of inclination angle and incident shock Mach number on the inclined interface RMI.…”
Section: Introductionmentioning
confidence: 99%
“…In the weakly nonlinear growth regime, for an initial single-mode cosine interface perturbation within the framework of third-order perturbation theory, [6,[12][13][14][15] the interface, up to the second order, can be expressed as…”
Section: Introductionmentioning
confidence: 99%